Portuguese Version of the Posttraumatic Stress Disorder Checklist for DSM-5 (PCL-5): Comparison of Latent Models and Other Psychometric Analyses - Carvalho, Teresa (2019)
Objective: This psychometric study explores the Portuguese version of the Posttraumatic Stress Disorder (PTSD) Checklist (PCL-5). It aims to clarify the bestfitting latent structure among competing PTSD models (DSM-5, Dysphoria, Dysphoric Arousal, Anhedonia, Externalizing Behavior, and Hybrid models) and its implications for PTSD measurement. Method: Psychometric analyses were conducted in a sample from the general population of firefighters (N = 466), except the temporal stability, which was tested in a subsample of 100 participants. Results: The models presented significant differences in global fit. The Hybrid model presented the best-fitting structure, but the DSM-5 model showed more favorable reliability and convergent validity in Confirmatory Factor Analyses. The DSM-5 model also proved to be internal consistency, temporal reliability, and convergent validity. Conclusion: The Portuguese version of PCL-5 is reliable and valid. The findings suggest the appropriateness of the DSM-5 model to assess PTSD symptomatology, encouraging its use in clinical and research settings.